Breast cancer in women: a descriptive analysis of the national cancer database - Sisti, Andrea (Acta Biomed, 2020)
BACKGROUND AND AIM OF THE WORK: Breast cancer is the most common cancer in women in the United States. National Cancer Database (NCDB) is one of the largest tumor databases of the United States. This study aimed to evaluate the features of breast cancer in women from a large updated database. METHODS: We describe and analyze the frequencies and percentages of the clinical and pathological features of women diagnosed with breast cancer registered in NCDB, in a period from 2004 to 2015. RESULTS: A total of 2,423,875 women were diagnosed with breast cancer between 2004 and 2015. The nationally representative analysis demonstrated that the incidence of breast cancer among women increased over the years. Upper-outer quadrant was the most frequent primary tumor site, and the intraductal carcinoma was the most frequent histology. The prevalence of breast cancer increased with age. The most frequent grade at diagnosis was grade II. Broadly, invasive characteristics were noted more frequently in younger patients. Left and right breast were affected with almost the same frequency, with a slight predominance of the left breast. The most frequent surgical treatment was a partial mastectomy. Reconstruction with implant was the most frequent choice. Post-mastectomy radiation therapy was administered in the majority of patients. CONCLUSIONS: To the authors’ knowledge, the current study is the largest descriptive analysis to date on the clinical and pathological features of breast cancer in a population-based database. The increase in incidence over the years indicates an important need for etiologic research and innovative approaches to improve breast cancer prevention. (www.actabiomedica.it)